2020
DOI: 10.1055/a-1031-9436
|View full text |Cite
|
Sign up to set email alerts
|

Anti-reflux mucosal ablation (ARMA) as a new treatment for gastroesophageal reflux refractory to proton pump inhibitors: a pilot study

Abstract: Background The incidence of proton pump inhibitor (PPI)-refractory gastroesophageal reflux disease (GERD) has been increasing. While surgical intervention with Laparoscopic Nissen Fundoplication remains the gold standard, less invasive anti-reflux interventions are desired. We have developed a minimally invasive anti-reflux mucosal ablation (ARMA) treatment. Herein, we report its technical details and describe its feasibility, safety, and efficacy in PPI-refractory GERD. Methods We conducted a prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 14 publications
0
82
0
2
Order By: Relevance
“…For instance, we could consider performing EPSIS on patients who are refractory to current therapies, such as PPI‐refractory GERD or radiofrequency ablation‐resistant BE patients. If the results of EPSIS show poor LES competences (i.e., a flat pattern and low IGP‐max), it could favour anti‐reflux treatments, such as laparoscopic anti‐reflux surgery or anti‐reflux mucosal ablation 22. Another potential application of EPSIS could be evaluating the effect of anti‐reflux surgery by performing EPSIS before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we could consider performing EPSIS on patients who are refractory to current therapies, such as PPI‐refractory GERD or radiofrequency ablation‐resistant BE patients. If the results of EPSIS show poor LES competences (i.e., a flat pattern and low IGP‐max), it could favour anti‐reflux treatments, such as laparoscopic anti‐reflux surgery or anti‐reflux mucosal ablation 22. Another potential application of EPSIS could be evaluating the effect of anti‐reflux surgery by performing EPSIS before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ARMS is an endoscopic procedure that does not address significantly disrupted EGJ anatomy, as defined by sliding hiatal hernia >3 cm or endoscopic Hill grade IV. 38 Given the resulting scarring at the EGJ with risk of postoperative dysphagia, ARMS is also contraindicated in the presence of esophageal dysmotility. 39,40 For patients with normal motility who don't qualify for ARMS and MSA, or prefer a time-tested laparoscopic approach, the decision between Toupet and Nissen can be guided by impedance planimetry in the operating room.…”
Section: Normal Esophageal Motilitymentioning
confidence: 99%
“…A pilot study of 12 patients recently published demonstrated a significant improvement in GERD-HRQL scores and a reduction in DeMeester scores. 16 Concerns about severe complications, including refractory stricture, dysphagia, and chest pain, as well as rare esophageal perforation, have prevented ARMS from being fully adopted by the surgical and endoscopic community. Further studies are needed to evaluate whether ARMA is a safer alternative with less significant potential side effects.…”
Section: Antireflux Mucosectomymentioning
confidence: 99%
“…The Inoue group has since modified their ARMS technique to a simplified version, the antireflux mucosal ablation (ARMA). A pilot study of 12 patients recently published demonstrated a significant improvement in GERD‐HRQL scores and a reduction in DeMeester scores 16 . Concerns about severe complications, including refractory stricture, dysphagia, and chest pain, as well as rare esophageal perforation, have prevented ARMS from being fully adopted by the surgical and endoscopic community.…”
Section: Antireflux Mucosectomymentioning
confidence: 99%